Headache characteristics in COVID-19 pandemic-a survey study - Uygun, Özge; Ertaş, Mustafa; Ekizoğlu, Esme; Bolay, Hayrunnisa; Özge, Aynur; Kocasoy Orhan, Elif; Çağatay, Arif Atahan; Baykan, Betül (Journal of headache and pain, 2020)
Background Headache is the most common COVID-19-related neurological symptom. We aimed to reveal diagnostic clues of headache for COVID-19 infection and to investigate the course of primary headaches during the pandemic. Methods We developed a detailed web-based questionnaire screening the characteristics and course of headaches besides clinical COVID-19 features. The participants were grouped according to being diagnosed with COVID-19 infection or not, and having previous or new-onset headaches. The COVID-19 related headache features and their associations with other clinical features were investigated. A binary logistic regression model was performed to differentiate the characteristics of headache related to COVID-19. Findings A total of 3458 participants (2341 females;67.7%, 1495 healthcare workers;43.2%) with a mean age of 43.21 ± 11.2 years contributed to the survey. Among them, 262 participants had COVID-19 diagnosis and 126 (48.1%) were male. The rate of males in the group without COVID-19 was 31% (991 out of 3196 participants) showing significant gender difference between groups ( p < 0.000). COVID-19 related headaches were more closely associated with anosmia/ageusia and gastrointestinal complaints ( p < 0.000 and p < 0.000), and showed different characteristics like pulsating, pressing, and even stabbing quality. Logistic regression analyses showed that bilateral headache, duration over 72 h, analgesic resistance and having male gender were significant variables to differentiate COVID-19 positive patients from those without COVID-19 ( p = 0.04 for long duration and p < 0.000 for others). A worsening of previous primary headaches due to the pandemic-related problems was not reported in the majority of patients. Interpretation Bilateral, long-lasting headaches, resistance to analgesics and having male gender were more frequent in people with COVID-19 in conjunction with anosmia/ageusia and gastrointestinal complaints. These features may be helpful for diagnosing the headache related to COVID-19 during the pandemic.